2019
DOI: 10.1002/wcms.1450
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning and artificial neural network accelerated computational discoveries in materials science

Abstract: Artificial intelligence (AI) has been referred to as the "fourth paradigm of science," and as part of a coherent toolbox of data-driven approaches, machine learning (ML) dramatically accelerates the computational discoveries. As the machinery for ML algorithms matures, significant advances have been made not only by the mainstream AI researchers, but also those work in computational materials science. The number of ML and artificial neural network (ANN) applications in the computational materials science is gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 197 publications
(319 reference statements)
0
56
0
1
Order By: Relevance
“…In principle, it can be considered that the remaining compounds belonged to the structure type labeled as "others", since these compounds did not match the provided definition of the crystal structure types. For this second test, 4S4O, 6S4O, 6S8O, and 6S10O ANNs were tested with 12,264,19,229,18,179, and 16,667 compounds, respectively. The difference in the number of compounds used in the second test depended on the number of compounds in the traval and test sets.…”
Section: Classification Of Crystal Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, it can be considered that the remaining compounds belonged to the structure type labeled as "others", since these compounds did not match the provided definition of the crystal structure types. For this second test, 4S4O, 6S4O, 6S8O, and 6S10O ANNs were tested with 12,264,19,229,18,179, and 16,667 compounds, respectively. The difference in the number of compounds used in the second test depended on the number of compounds in the traval and test sets.…”
Section: Classification Of Crystal Compoundsmentioning
confidence: 99%
“…In recent years, machine learning algorithms have irrupted as an alternative tool to model the properties and structure of materials [1][2][3][4][5][6][7][8][9][10][11]. These algorithms have allowed scientists to work with large particle systems at shorter times and lower computational costs with respect to the recurred quantum methods [12][13][14][15]. Agrawal and Choudhary [16] have suggested that machine learning constitutes nowadays a fourth modeling paradigm in science, which relies on the information stocked in large databases.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of Machine Learning (ML) and Deep Learning (DL) approaches have created a path towards solving previously challenging unsolved problems in biology and chemistry [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Various reviews summarize the application of ML/DL in drug design and discovery [ 18 , 19 , 20 , 21 , 22 ]. ML-based PLI prediction has been developed from a chemogenomic perspective [ 23 ] that considers interactions in a unified framework from chemical space and proteomic space.…”
Section: Introductionmentioning
confidence: 99%
“…9 Machine learning (ML) and Deep learning (DL) approaches have recently received attention in this field. Various reviews summarize the application of ML/DL in drug design and discovery [10][11][12][13][14] . Machine learning based PLI prediction has been developed from a chemogenomic perspective 15 that considers interactions in a unified framework from chemical space and proteomic space.…”
Section: Introductionmentioning
confidence: 99%